Target-independent cholinergic differentiation in the rat sympathetic nervous system - Schäfer, Martin K.-H. (National Academy of Sciences, 1997)
Chemical coding in the sympathetic nervous system involves both noradrenergic and, for a minority of neurons, cholinergic neurotransmission. The expression of the cholinergic phenotype in the developing sympathetic nervous system was examined to determine if coding for cholinergic transmission occurs before or after innervation of peripheral target organs. The vesicular acetylcholine transporter (VAChT) and choline acetyltransferase, the products of the “cholinergic gene locus” determining the cholinergic phenotype, were expressed in principal cells of the paravertebral, but only rarely in prevertebral, sympathetic chains as early as embryonic day 14. A subpopulation of VAChT- and choline acetyltransferase-positive sympathetic ganglion cells persisted throughout development of the stellate and more caudal paravertebral ganglia into anatomically distinct cell groups, and into adulthood. The forepaw eccrine sweat glands, innervated exclusively by the stellate ganglion, received VAChT-positive nerve terminals at least as early as postembryonic day 4, coincident with the development of the sweat glands themselves. These terminals, like the VAChT-positive cell bodies of the developing stellate ganglion, have some noradrenergic traits including expression of tyrosine hydroxylase, but did not express the vesicular monoamine transporter, and are therefore not functionally noradrenergic. Development of the cholinergic phenotype in principal cells of the sympathetic paravertebral ganglia apparently occurs via receipt of instructive cues, or selection, within the sympathetic chain itself or perhaps even during migration of the cells of the neural crest from which the paravertebral ganglia arise.